2020
DOI: 10.21203/rs.3.rs-46825/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the therapeutic effect of high-flow nasal cannula oxygen therapy on patients with aspiration pneumonia accompanied by respiratory failure in the post-stroke sequelae stage

Abstract: Background: The aim of the present study was to evaluate the therapeutic effect of high-flow nasal cannula (HFNC) oxygen therapy on patients with aspiration pneumonia accompanied by respiratory failure in the post-stroke sequelae stage, with the goal of providing more effective oxygen therapy and improving patient prognosis. Methods: Retrospective analysis was conducted on 103 elderly patients with post-stroke aspiration pneumonia and moderate respiratory failure (oxygenation index: 100–200 mmHg) that had been… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…[4] The poststroke sequelae mainly refer to a condition left after hemorrhage of acute cerebrovascular disease, hemiplegia, numbness, skewed eyes, and poor speech. [5,6] At present, stroke, cancer, and coronary heart disease have become the 3 major diseases of human death in the world, which poses a serious threat to the safety of patients' lives and physical and mental health. In recent years, more and more reports have shown that acupuncture combined with traditional Chinese medicine has a significant effect in the treatment of sequelae of stroke, which can improve the patient's nerve function and limb function, relieve the symptoms of sequelae, and improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The poststroke sequelae mainly refer to a condition left after hemorrhage of acute cerebrovascular disease, hemiplegia, numbness, skewed eyes, and poor speech. [5,6] At present, stroke, cancer, and coronary heart disease have become the 3 major diseases of human death in the world, which poses a serious threat to the safety of patients' lives and physical and mental health. In recent years, more and more reports have shown that acupuncture combined with traditional Chinese medicine has a significant effect in the treatment of sequelae of stroke, which can improve the patient's nerve function and limb function, relieve the symptoms of sequelae, and improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is currently the leading cause of death and disability in our population, and about 2 million strokes occur every year in China [4] . The poststroke sequelae mainly refer to a condition left after hemorrhage of acute cerebrovascular disease, hemiplegia, numbness, skewed eyes, and poor speech [5,6] . At present, stroke, cancer, and coronary heart disease have become the 3 major diseases of human death in the world, which poses a serious threat to the safety of patients’ lives and physical and mental health.…”
Section: Introductionmentioning
confidence: 99%